Current status of forensic anthropology in the Middle East and North Africa (MENA) region - Mansour, Cindy; Márquez-Grant, Nicholas; Benito Sánchez, María (Springer, 2025)
Background Forensic anthropology has evolved significantly, from its foundations in the nineteenth century to its formal establishment in the twentieth century and in particular with modern advancements from the 1970s onward. Its role in human rights investigations during the 1980s in Latin America and the 1990s in the Balkans, exemplifies its global impact. However, the practice and application of forensic anthropology in the Middle East and North Africa (MENA) region remain underexplored. This study assesses the current status of forensic anthropology in this region through a brief literature review and online interviews with academics and practitioners in forensic anthropology or closely related disciplines. The interviews addressed the medico-legal system structure, forensic science capabilities, training efforts, practitioner availability, case types (medico-legal and humanitarian), and resources like radiological imaging. Results The study revealed that forensic anthropology is largely underutilized in the MENA region’s medico-legal death investigation systems. Factors such as limited human capital, lack of discipline awareness, varying legal and procedural systems, and insufficient academic infrastructure hinder its integration. Challenges include political instability, safety concerns for practitioners, and inadequate resources. The study highlights ongoing efforts by practitioners to improve the field through theoretical and practical training, capacity building, and resource development. Conclusion The findings underscore the need for strategic investments to strengthen forensic anthropology in the MENA region. Recommendations include enhancing education and training, fostering interdisciplinary collaboration, disseminating scientific knowledge, increasing access to resources, and revising medico-legal frameworks. These measures can bridge existing gaps and advance forensic anthropology’s role in medico-legal and humanitarian contexts.
Keywords: 4804 Law In Context; 48 Law and Legal Studies; 44 Human Society; Forensic anthropology; Forensic science; Middle East; North Africa; MENA region; Survey